Case Report: Long-Term Survival With Anlotinib in a Patient With Advanced Undifferentiated Large-Cell Lung Cancer and Rare Tonsillar Metastasis - Xu, Tianwei; Wei, Chenchen; Zou, Xiaoteng; Lu, Binbin; Wang, Zhaoxia (Frontiers in Oncology, 2021)
Undifferentiated large-cell lung cancer is a rare type of non-small cell lung cancer (NSCLC) with a poor prognosis. It is insensitive to chemotherapy and easily develops drug resistance. Analysis of the Surveillance, Epidemiology, and End Results (SEER) database showed that patients with stage IV undifferentiated large-cell lung cancer had a median overall survival (OS) of only 4 months and that those who received chemotherapy had a median OS of only 5 months longer than those who did not. For the first time, we report a case of advanced large-cell undifferentiated lung cancer with rare tonsil metastasis. The patient developed resistance after 3 months of platinum-based systemic chemotherapy and local treatment. Antiangiogenic therapy has been continuously progressing and has shown certain efficacy in treating many malignant tumors, such as lung cancer. However, there are no relevant studies or case reports on antiangiogenic therapy in the treatment of undifferentiated large-cell lung cancer. Anlotinib, an orally delivered small-molecule antiangiogenic tyrosine kinase inhibitor (TKI), was administered to this patient after chemotherapy resistance occurred, and the outcome was assessed as continued stable disease (SD). As of the last follow-up evaluation, the progression-free survival (PFS) of the patient was 21.5 months, and the OS was 27.5 months. Retrospective immunohistochemical analysis showed that the patient was positive for one of the targets of anlotinib (PDGFR). In general, the findings in this case suggest that anlotinib may be an option with good efficacy for patients with large-cell undifferentiated lung cancer after chemotherapy resistance that may have good efficacy and also suggest that PDGFR may be the target underlying this effect.